The Influence of Organizational Support to Knowledge Sharing at Universities in Indonesia - Komala Puti, Ratna; Gumilar Sambas, Ivan; Hendri, Meriza; Nilasari, Irma (International Journal of Psychosocial Rehabilitation, 2020)
Objective: To produce a study of organizational support for knowledge sharing (KS) in private universities in Indonesia. Design/method/approach: Combined qualitative and quantitative research, the test tool uses SEM (Structural Equation Modeling) for the verification hypothesis. Whereas for qualitative research with FGD and interviews. Originality/value—based on searches from several previous studies—shows that research on the influence of organizational support for knowledge sharing has never existed. So that this research can be used as literature to increase knowledge sharing in the university environment. Findings: Increasing sharing of knowledge in higher education institutions can be carried out effectively if organizational support is enhanced.